Applied research and evaluation in community mental health services : an update of key research domains - Vingilis, Evelyn; State, Stephen A., 1949- (McGill-Queen's University Press, 2011)
The burden of mental illness on individuals, families, and communities has created profound challenges for our society. In recent years treatments and services for the mentally ill have moved almost exclusively to community settings, yet no comprehensive and progressive policies have emerged to counter stigmatizing and facilitate integration.